2010
DOI: 10.1007/s11258-010-9739-4
|View full text |Cite
|
Sign up to set email alerts
|

Flower heliotropism of Anemone rivularis (Ranunculaceae) in the Himalayas: effects on floral temperature and reproductive fitness

Abstract: The flower heliotropism of Anemone rivularis (Ranunculaceae) was investigated on the Yulong Snow Mountain, near Lijiang in the northwest of the Yunnan province of China. We discovered that tepals in this species drive the peduncles to track the sun, and that this flower heliotropism was likely an adaptation for parental environmental effects on reproductive fitness. In brief, A. rivularis flowers retained sun-tracking behavior following removal of pistils and stamens, but lost heliotropic movement, if tepals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Ecological factors might influence a flower’s capability to generate temperature patterns pollinators can detect. The amount of sunlight captured limits floral warming in non-thermogenic plants ( Totland, 1996 ; Rejšková et al, 2010 ; Zhang et al, 2010 ). While Rejšková et al, 2010 found that artificially shaded Bellis perennis flowers maintained temperature patterns, overall temperature of the flower and temperature contrast between regions decreased, and shaded Anemone nemorosa cooled to even temperature across the flower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecological factors might influence a flower’s capability to generate temperature patterns pollinators can detect. The amount of sunlight captured limits floral warming in non-thermogenic plants ( Totland, 1996 ; Rejšková et al, 2010 ; Zhang et al, 2010 ). While Rejšková et al, 2010 found that artificially shaded Bellis perennis flowers maintained temperature patterns, overall temperature of the flower and temperature contrast between regions decreased, and shaded Anemone nemorosa cooled to even temperature across the flower.…”
Section: Discussionmentioning
confidence: 99%
“…One flower cue bees can use to recognise flowers is floral temperature ( Whitney et al, 2008 ; Hammer et al, 2009 ; Norgate et al, 2010 ). Warming of flowers can occur due to floral thermogenesis ( Seymour and Schultze-Motel, 1997 ; Seymour and Matthews, 2006 ; Seymour et al, 2009 ), but is more frequently the result of captured solar radiation ( Totland, 1996 ; Sapir et al, 2006 ; Rejšková et al, 2010 ; Zhang et al, 2010 ; Atamian et al, 2016 ). The absorption of sunlight and heat loss is influenced by pigmentation ( Kay et al, 1981 ; Sapir et al, 2006 ), structure ( Rejšková et al, 2010 ; Whitney et al, 2011 ) and heliotropism ( Totland, 1996 ; Zhang et al, 2010 ; Atamian et al, 2016 ), all of which will contribute to how much a certain flower will heat up in given conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, there is often a biological reason to include monitoring of these environmental factors independent of their influence on thermography. This is especially true of environmental temperature, a key biological variable [18]. This means even without any knowledge of what parameters needed to be entered into the camera, and included in the report, it is likely authors would have monitored and reported these environmental parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature is an important biological variable. It is a key influence on living organisms [18], and temperature can also be used as an indicator for metabolic activity [7,911], disease, injury and stress [1216]. Temperature of organisms has been measured using thermocouples [1719] or thermistors [20,21], though use of thermographic cameras has increased dramatically in recent years with improvement of the technology [14,22].…”
Section: Introductionmentioning
confidence: 99%
“…ex DC. (Ranunculaceae, Zhang et al, ). For instance, He et al () found that flowers of G. straminea close when the air temperature falls sufficiently, thereby protecting pollen grains from rainfall and increasing both male and female fitness.…”
Section: Specialized Morphological Adaptations Of Plants In the Qtpmentioning
confidence: 99%